In Ole Virginia: Or, Marse Chan and Other Stories - Page, Thomas Nelson (J.S. Sanders, 1991)
More than any other writer, Thomas Nelson Page created the elegiac image of the “Old South,” a garden world of noble cavaliers and faithful retainers that has left its mark on the popular imagination to this day. The popularity of these stories, told with such sincere charm and affection, helped greatly to heal the wounds of the nation, restoring to the defeated South a sense of pride in its culture, and reminding Northern audiences of the virtues of their former foes. Representing the finest of page’s writings, these evocations of both the pre-war and post-war South are told by the freed men and women who are its particular heroes.